Relative signs of 29Si-13C couplings - Blechta, Vratislav (Magnetic resonance in chemistry : MRC, 2008)
Two pulse sequences applicable to the determination of relative signs of coupling constants, gHSQC-RELAY(P) and gHSQC-RELAY(D), were developed and tested. These sequences are suitable for determination of relative signs of long-range coupling constants (<2 Hz) between two heteronuclei of low abundance (such as (29)Si and (13)C), and are applicable even to cases in which one of the heteronuclei ((29)Si) does not exhibit coupling with some of the detected protons ((1)H). The two sequences differ in the manner in which they suppress undesirable homonuclear coherence transfers. Each of the sequences can be combined with an isotope filter for better suppression of the centerlines arising from more abundant NMR-inactive isotopes. The sequences were tested on ethoxytrimethylsilane and (E)-(buta-1,3-dienyloxy)trimethylsilane, and we conclude that (2)J((29)Si-O-(13)C) is positive while (3)J((29)Si-O-C-(13)C) is negative in both compounds